Manliness and Space In Rabindranath Tagore’S Short Stories: Exploring Gender and Geography in Tagore's Literary Works (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Tagore’s novels have been studied withdifferent perspectives viz. East-West encounter, humanism, love, andnationalism among others. He lived in the time when the forces of the IndianRenaissance had spread in all directions. Tagore’s novels reflect the spirit ofthe age with keenness and fidelity. Tagore sensed the genuine social changethrough new education and the emergence of woman as a social power. Tagore wasa conscious and sensitive writer who knew that the contribution of women tohuman evolution can never be overlooked. Though he never believed that womanwas inferior to man, he sincerely believed that a woman’s domain was differentfrom that of a man. Even though she could, she did not prefer to play the samerole as man, in the society. Tagore’s literary works knew no geographicalboundaries, and as a result, he came to be known as world-apostle. His workshave been translated into English and other languages too. Tagore, himself,also translated some of his works into English.